2007
DOI: 10.1016/j.iccn.2007.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The meaning of posttraumatic stress-reactions following critical illness or injury and intensive care treatment

Abstract: Traumatic events connected with a critical condition and treatment in the intensive care unit (ICU) may result in subsequent posttraumatic stress-reactions. The aim of this phenomenological study was to describe the meaning of posttraumatic stress-reactions as experienced by individuals following a critical illness or injury and intensive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 34 publications
1
46
2
1
Order By: Relevance
“…To gain insights into the complexity of issues after an episode of critical illness, qualitative research may be used [2,3]. Qualitative studies with ICU survivors and their family caregivers have primarily examined needs during the ICU stay, relocation stress experienced while transitioning from the ICU, and posttraumatic stress disorder [4,5]. These studies suggest that relocation stress may be minimized by addressing practical causes such as communication issues experienced by survivors who have had a tracheostomy and nursing care that is more sensitive to survivors' specialized needs [4,5], whereas posttraumatic stress disorder can be reduced by decreasing the patient's distress and fear and lessening the impact of ICU stressors while maintaining a calm environment [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To gain insights into the complexity of issues after an episode of critical illness, qualitative research may be used [2,3]. Qualitative studies with ICU survivors and their family caregivers have primarily examined needs during the ICU stay, relocation stress experienced while transitioning from the ICU, and posttraumatic stress disorder [4,5]. These studies suggest that relocation stress may be minimized by addressing practical causes such as communication issues experienced by survivors who have had a tracheostomy and nursing care that is more sensitive to survivors' specialized needs [4,5], whereas posttraumatic stress disorder can be reduced by decreasing the patient's distress and fear and lessening the impact of ICU stressors while maintaining a calm environment [5].…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative studies with ICU survivors and their family caregivers have primarily examined needs during the ICU stay, relocation stress experienced while transitioning from the ICU, and posttraumatic stress disorder [4,5]. These studies suggest that relocation stress may be minimized by addressing practical causes such as communication issues experienced by survivors who have had a tracheostomy and nursing care that is more sensitive to survivors' specialized needs [4,5], whereas posttraumatic stress disorder can be reduced by decreasing the patient's distress and fear and lessening the impact of ICU stressors while maintaining a calm environment [5]. One study exploring the needs of ICU survivors with acute respiratory distress syndrome (ARDS) beyond the ICU transition phase found that needs for information and support changed from the early ICU stages through survivors' adjustment to life at home [1].…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies focused specifically on long-term psychological effects and more specifically incidences of PTSD following ICU discharge (Corrigan et al, 2007;Davydow et al, 2008). Scott & Palmer (2000) argued that PTSD can be diagnosed in an individual who, following a stressful event, presents with symptoms of intrusion, avoidance and disordered arousal.…”
Section: Introductionmentioning
confidence: 99%
“…Van Horn and Tesh (2000) reported that the most important care for families is that provided by other family members and friends. Families that experience acute and critical illness and injury may be exposed to double-stress due to double trauma (Corrigan et al, 2007). For multicultural patients and families, double-stress in hospital as well as dependency and raw emotions could be triggered by their previous traumatic experiences as immigrants or refugees.…”
Section: Introductionmentioning
confidence: 99%